870000 LEGISLATIVE REPORT STATE LEGISLATIVE ACTIVITY MAJOR TOBACCO ISSUES FINAL SUMMARY VOLUME I (Tufts Archival Research Center, 2007)
Legislative summary for the year 1987. Contains reports and summaries of all the major issues facing the tobacco industry that year including excise taxes, anti smoking legislation and fire safe cigarettes among many others.